(untitled) (International journal of artificial intelligence, 2026)
This article examines the integration of bionics-based (biomimicry-inspired) learning approaches to develop creative thinking skills among preschool-aged children (typically 4–6 years old). Bionics, which involves emulating nature’s designs, processes, and systems to solve human challenges, provides a powerful, engaging framework for early childhood education. By encouraging children to observe biological phenomena and adapt them creatively, educators can foster key components of creativity such as fluency, flexibility, originality, and elaboration. The study combines a comprehensive literature review, theoretical foundations from educational psychology and biomimicry, and empirical insights from a pilot implementation in preschool settings. Practical activities include nature observation walks, design challenges mimicking animal adaptations (e.g., bird wings for flight or lotus leaves for self-cleaning), storytelling with bionic themes, and hands-on prototyping with recycled materials. Results indicate significant improvements in creative thinking metrics, enhanced curiosity, problem-solving abilities, and collaborative skills. The approach aligns with child-centered pedagogies and supports Uzbekistan’s national preschool curriculum goals for holistic development. This method not only nurtures creativity but also promotes environmental awareness and interdisciplinary thinking, preparing young learners for future innovation.